Distinct Pattern of Gray Matter Atrophy in Mild Alzheimer's Disease Impacts on Cognitive Outcomes of Noninvasive Brain Stimulation - Anderkova, Lubomira; Eliasova, Ilona; Marecek, Radek; Janousova, Eva; Rektorova, Irena (Journal of Alzheimer's disease, 2015)
BACKGROUND: Repetitive transcranial magnetic stimulation (rTMS) is a promising tool to study and modulate brain plasticity. OBJECTIVE: Our aim was to investigate the effects of rTMS on cognitive functions in patients with mild cognitive impairment and Alzheimer's disease (MCI/AD) and assess the effect of gray matter (GM) atrophy on stimulation outcomes. METHODS: Twenty MCI/AD patients participated in the proof-of-concept controlled study. Each patient received three sessions of 10 Hz rTMS of the right inferior frontal gyrus (IFG), the right superior temporal gyrus (STG), and the vertex (VTX, a control stimulation site) in a randomized order. Cognitive functions were tested prior to and immediately after each session. The GM volumetric data of patients were: 1) compared to healthy controls (HC) using source-based morphometry; 2) correlated with rTMS-induced cognitive improvement. RESULTS: The effect of the stimulated site on the difference in cognitive scores was statistically significant for the Word part of the Stroop test (ST-W, p = 0.012, linear mixed models). As compared to the VTX stimulation, patients significantly improved after both IFG and STG stimulation in this cognitive measure. MCI/AD patients had significant GM atrophy in characteristic brain regions as compared to HC (p = 0.029, Bonferroni corrected). The amount of atrophy correlated with the change in ST-W scores after rTMS of the STG. CONCLUSION: rTMS enhanced cognitive functions in MCI/AD patients. We demonstrated for the first time that distinct pattern of GM atrophy in MCI/AD diminishes the cognitive effects induced by rTMS of the temporal neocortex.
Keywords: senioři; psychiatrické posuzovací škály; Psychiatric Status Rating Scales; senioři nad 80 let; Neuropsychological Tests; transkraniální magnetická stimulace; Analysis of Variance; Alzheimer’s disease; výsledek terapie; Cognition Disorders; mužské pohlaví; cognitive functions; Gray Matter; Alzheimer Disease; brain atrophy; analýza rozptylu; noninvasive brain stimulation; source-based morphometry; kognitivní poruchy; Aged, 80 and over; mozková kůra; ženské pohlaví; šedá hmota; neuropsychologické testy; Humans; Cerebral Cortex; Alzheimerova nemoc; Female; Aged; Transcranial Magnetic Stimulation; Treatment Outcome; lidé; Male